2021
DOI: 10.3390/cancers13143580
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differentially Methylated Genes in Vulvar Squamous Cell Carcinoma

Abstract: DNA methylation is the most widely studied mechanism of epigenetic modification, which can influence gene expression without alterations in DNA sequences. Aberrations in DNA methylation are known to play a role in carcinogenesis, and methylation profiling has enabled the identification of biomarkers of potential clinical interest for several cancers. For vulvar squamous cell carcinoma (VSCC), however, methylation profiling remains an under-studied area. We sought to identify differentially methylated genes (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…However, the vast majority of HSILs demonstrated a uniform diffuse p16 INK4a staining pattern, while both high and low methylation levels were seen, indicating heterogeneity of vulvar HSILs. This observation is in agreement with earlier studies showing that morphologically identical vulvar HSILs show substantial molecular heterogeneity with respect to both copy number aberrations (CNA) and DNA methylation, despite similar histopathological classification and p16 INK4a /Ki-67 staining patterns [ 14 , 15 , 18 ]. This heterogeneity is also seen in cervical and anal p16 INK4a -positive HSIL, with a subset of those high-grade anogenital lesions having as high methylation levels as cancer [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the vast majority of HSILs demonstrated a uniform diffuse p16 INK4a staining pattern, while both high and low methylation levels were seen, indicating heterogeneity of vulvar HSILs. This observation is in agreement with earlier studies showing that morphologically identical vulvar HSILs show substantial molecular heterogeneity with respect to both copy number aberrations (CNA) and DNA methylation, despite similar histopathological classification and p16 INK4a /Ki-67 staining patterns [ 14 , 15 , 18 ]. This heterogeneity is also seen in cervical and anal p16 INK4a -positive HSIL, with a subset of those high-grade anogenital lesions having as high methylation levels as cancer [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Gene silencing leads to loss of the tumor suppressive function, thereby contributing to cancer development [ 13 ]. In recent years, DNA methylation of specific genes has shown to be a promising biomarker in the identification of anogenital lesions, including vulvar neoplasia [ 13 , 15 , 16 , 17 , 18 ]. It has been demonstrated that methylation levels of 12 genes significantly increase from healthy vulvar tissue toward vulvar cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has demonstrated that LINC00304 directly promotes cell proliferation and cell cycle progression in prostate cancer (47). PRICKLE2-AS1 has been shown to be differentially methylated in vulvar squamous cell carcinoma (48) and FAM13A-AS1 is involved in regulating RNA splicing and mRNA processing in thyroid cancer (49). Herein, PRICKLE2-AS1, FAM13A-AS1, and LINC00304 were shown to be downregulated in ESCA tumors, whereas C15orf54 was upregulated (log 2 FC =1.51; q value =0.02).…”
Section: Discussionmentioning
confidence: 94%
“…Evidence suggests that E7 of HPV is able to induce CCNA1 promoter methylation by forming a complex with Dnmt1 [ 32 ]. In a recently performed genome-wide methylation sequencing on a set of 18 VSCC and 6 normal vulvar tissue, 199 genes were found to be differentially methylated, without CCNA1 being among them [ 19 ]. An explanation for this might be the small sample size of HPV induced cancers ( n = 3) in their cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al reported PI3KCA mutations, but also high numbers of copy number gains, leading to a PIK3CA alteration rate of 60% in their HPV positive cohort. Recently, methylation profiling was performed in a set of 18 primary VSCC, including 3 HPV+ samples and compared to normal tissue [ 19 ]. Most of the genes that were found to be hypermethylated in VSCCs (e.g., ZSCAN1, ZNF135, ZNF471, or TBX3) are involved in transcription regulator activity.…”
Section: Introductionmentioning
confidence: 99%